The Study Of Rainwater Harvesting System For Supporting Green Campus - Syarifah Amatullah (Journal of Environmental Engineering and Waste Management, 2023)
Water is one of the most important elements for humans but nowadays, the growing demand for clean water and increasing water scarcity are serious issues that must be addressed. As an alternative solution, optimizing the use of high-intensity rain in Indonesia through a Rainwater Harvesting system can help and support the water conservation efforts conducted in the green campus concept. The purpose of this final project is to calculate the cost and saving possibility through applying the rainwater harvesting system both in terms of water saving possibility and economic saving and provide the design of a rainwater harvesting system unit that is suitable for the Building A of President University. The observation method was used in this final project to find out what is the water quality of the rainwater harvested and also used the documentation method for processing the secondary data. Using the given rainfall data, the rainwater supply, in year water saving through the use of rainwater harvesting system can reach around 148.8 – 154 m3/year and save around Rp. 208,320 over the year for water costs. The storage tank capacity of the system was the size of 840 liters with the gutter 9 inches in diameter and the distribution pipe diameter 8 inches.